Changes in Impairment Loss Allowances on Receivables Under PSAK 71: Perubahan Cadangan Kerugian Penurunan Nilai Piutang Berdasarkan PSAK 71 - Putri, Aprilia; Surifah, Surifah (Academia Open, 2025)
General Background: Transparency and accuracy in financial reporting are crucial for publicly listed companies, especially in the banking sector. Specific Background: The adoption of PSAK 71 in 2020, replacing PSAK 55, introduced the Expected Credit Loss (ECL) model to enhance credit risk recognition in Indonesia’s financial system. Knowledge Gap: Previous studies lacked longitudinal data spanning pre-, during-, and post-crisis periods to capture the full impact of this standard. Aim: This study analyzes changes in allowance for impairment losses (CKPN) on receivables before and after PSAK 71 implementation in Indonesian banking companies listed on the IDX from 2015 to 2023. Results: The findings reveal a statistically significant increase in CKPN post-implementation, indicating more conservative credit risk estimations and improved accuracy in financial reporting. Novelty: This research uniquely covers a comprehensive time frame including the COVID-19 crisis, and applies both parametric (t-test) and non-parametric (Mann–Whitney U) tests, ensuring robust statistical validation. Implications: The results provide empirical support for standard-setters, regulators, auditors, and banking practitioners, highlighting PSAK 71’s role in strengthening financial statement reliability and credit risk management under various economic conditions. Highlight : Impairment reserves increased significantly after PSAK 71 implementation. ECL method better reflects future credit risk than incurred loss model. Validity strengthened by covering pre-, during-, and post-crisis periods. Keywords : CKPN; PSAK 71; Expected Credit Loss; Banking Sector; Financial Reporting